The influence of basin setting and turbidity current properties on the dimensions of submarine lobe elements. Issue 7 (29th May 2020) - Spychala, Yvonne T.; Eggenhuisen, Joris T.; Tilston, Mike; Pohl, Florian
Abstract: Submarine lobes have been identified within various deep‐water settings, including the basin‐floor, the base of slope and the continental slope. Their dimensions and geometries are postulated to be controlled by the topographic configuration of the seabed, sediment supply system and slope gradient. Ten experiments were conducted in a three‐dimensional‐flume to study the depositional characteristics of submarine lobes associated with: (i) different basin floor gradients (0 to 4°); (ii) different sediment concentrations of the parent turbidity current (11 to 19% vol); and (iii) varying discharge (25 to 40 m 3  h −1 ). Most runs produced lobate deposits that onlapped onto the lower slope. Deposit length was proportional to basin‐floor angle and sediment volume concentration. A higher amount of bypass is observed in the proximal area as the basin‐floor angles get steeper and sediment concentrations higher. Deposits of runs with lower discharge could be traced higher upslope while runs with higher discharge produced an area of low deposition behind the channel mouth, i.e. discharge controlled whether lobe deposits were attached or detached from their channel‐levée systems. A particle‐advection‐length scale analysis suggests that this approach can be used as a first order estimation of lobe element length. However, the estimations strongly depend on the average grain size used for calculations (for example, silt is still actively transported after all sand has been deposited) and the method cannot be used to locate the main depocentre. Furthermore, attempted reconstructions of turbidity current velocities from natural systems suggest that the method is not appropriate for use in inversions from more complex composite bodies such as lobes.